Evaluasi dan Desain Perbaikan Antarmuka Pengguna Pada Situs Web Funtech Plaza Menggunakan Metode Goal-Directed Design (GDD) - Panji Wicaksono; Retno Indah Rokhmawati; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Funtech Plaza is one of the technology-themed tourist attractions that is part of East Java Park 3. Funtech Plaza has a website that has plain-looking design problems and less informative content that requires improvements in terms of user interface and information architecture. The method used in this study is the Goal-Directed Design that is used to design websites in accordance with the goals of the user and to support the business goals of an organization. The Goal-Directed Design method consists of 6 phases. In this study only used 5 phases because it did not reach the implementation phase. In this study, interviews were conducted, to find out website problems, evaluations using the SUS questionnaire, identify content requirements, and make website prototypes. The results of the SUS test on the evaluation get an average value of 44 while the SUS test on the final evaluation gets an average value of 86.5 so that there are improvements in terms of acceptability ranges, grade scale, adjective ratings, and percentile ranks. From the results of user testing get more positive values ​​than negative values, so it can be concluded that there is an increase in the value of user satisfaction with the Funtech Plaza website.